Pemilihan Obat, Penyesuaian Dosis, dan Potensi Interaksi Antihipertensi dan Antidiabetes pada Pasien Penyakit Ginjal Kronis dengan Hemodialisis - Maria, Nisa; Susilo, Ferlina Vidyananda; Simarmata, Mayannaria (Faculty of Pharmacy, Universitas Pancasila, 2023)
Antihypertensive and antidiabetic drugs in CKD patients on hemodialysis may cause medication-related problems requiring monitoring. This study aimed to evaluate the selection, dosage, and potential drug interactions of antihypertensive and antidiabetic drugs in stage 5 CKD patients with hypertension and/or type 2 diabetes mellitus undergoing hemodialysis in a hospital in Jakarta. A crosssectional study used the medical records of adult in patients from January - December 2022 with a total sampling method. Out of 101 patients, 97.0% received appropriate drug selection. Dosage adjustments were appropriate in 74.3% of cases. Potential drug interactions between antihypertensive and antidiabetic drugs were found in 90.1% of patients, mostly pharmacodynamic interactions, moderate severity, and requiring monitoring. Statistical analysis showed that age, gender, number of drugs, and length of stay were not associated with the appropriateness of antihypertensive and antidiabetic drug selection (p>0.05). However, there was a relationship between number of drugs (p=0.033; OR=2.996) and length of stay (p=0.024; OR=3.171) with the appropriateness of drug dosage. The length of stay was also associated with potential drug interactions (p=0.040; OR=8.426). Drug selection has been done well, but there is a need for improvement in monitoring dosage adjustments and potential drug interactions by pharmacists in the hospital.